Optical Properties Of Crystal Materials - Mamatkulov Bakhodir Khatamovich; Mustafakulov Asror Akhmedovich (Zien Journals, 2024)
The optical properties of quartz crystal, their natural and artificial types, optical radiation spectra are given.
Keywords: crystal; mineral; structure